2020
DOI: 10.1001/jamacardio.2019.4296
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sex With Outcomes in Patients Undergoing Percutaneous Coronary Intervention

Abstract: IMPORTANCE Women experience worse ischemic and bleeding outcomes after percutaneous coronary intervention (PCI).OBJECTIVES To assess the association of sex with patient outcomes at 2 years after contemporary PCI and with the efficacy and safety of 2 antiplatelet strategies. DESIGN, SETTING, AND PARTICIPANTSThis study is a prespecified subgroup analysis of the investigator-initiated, prospective, randomized GLOBAL LEADERS study evaluating 2 strategies of antiplatelet therapy after PCI in an unselected populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 33 publications
3
57
1
1
Order By: Relevance
“…Congruent with recent studies of newer P2Y12 inhibitors 28,29) , this study showed an increased risk of bleeding in women compared with men. However, there was no significant difference between ticagrelor and prasugrel in women or men and no treatment arm-by-sex interaction with respect to the risk of bleeding with these drugs in both sexes.…”
Section: Discussionmentioning
confidence: 50%
“…Congruent with recent studies of newer P2Y12 inhibitors 28,29) , this study showed an increased risk of bleeding in women compared with men. However, there was no significant difference between ticagrelor and prasugrel in women or men and no treatment arm-by-sex interaction with respect to the risk of bleeding with these drugs in both sexes.…”
Section: Discussionmentioning
confidence: 50%
“…Similar to our registry, main independent predictors for cardiovascular mortality or non-fatal myocardial infarction were age, diabetes, smoking, prior MI, peripheral artery disease, but also prior stroke, atrial fibrillation, and history of hospitalization for heart failure. A pooled analysis of individual patient data regarding outcome after PCI [ 37 ], a subgroup analysis of the GLOBAL LEADERS trial [ 38 ], and a sex-related study on patients with acute myocardial infarction [ 39 ] also found no association of sex with long-term mortality. In contrast, 10 years ago Ezekowitz et al [ 17 ] reported on a higher 1-year mortality in women with CAD compared to men, but prescription rates for guideline-recommended medication were lower in that study than in our registry.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of individual patient data regarding outcome after PCI [37], a subgroup analysis of the GLOBAL LEADERS trial [38], and a sex-related study on patients with acute myocardial infarction [39] also found no association of sex with long-term mortality. In contrast, 10 years ago Ezekowitz et al [17] reported on a higher 1-year mortality in women with CAD compared to men, but prescription rates for guideline-recommended medication were lower in that study than in our registry.…”
Section: Outcome and Mortalitymentioning
confidence: 99%
“…Существуют гендерные различия в оценке прогноза заболевания после перенесенного ЧКВ. В ряде работ продемонстрирован более высокий риск осложнений ЧКВ у женщин по сравнению с мужчинами [14,15]. По результатам нашего исследования у женщин вдвое чаще встречались превышения ВГН Вч-Тр (40% против 70%, p=0,048), также чаще развивался ИМ 4а типа (21% против 3%, p<0,05).…”
Section: Discussionunclassified